A Comprehensive Study Using Field Observations and Numerical Simulation Techniques to Design a Mechanised Depillaring Panel - Gadepaka P.R.; Sonu; Jaiswal A. (My University, 2025)
Understanding the caving phenomenon is crucial for designing continuous miner panels. In India, some conventionally developed bord and pillar panels have been planned for mechanised depillaring using continuous miners (CM). This study examines strata behaviour during the mechanised depillaring operations of a panel initially developed for conventional mining by drilling and blasting. The panel comprises two sub-panels: the dip side with larger pillars and the rise side with smaller ones. Strata issues were particularly noticed on the rise side after extracting pillar number 54, where smaller pillars were present, leading to some pillars being left out. A three-dimensional numerical simulation study using FLAC3D was conducted to investigate the root cause of these strata-related issues. A previously proposed novel approach, which resembles the natural caving process, was implemented for the caving simulation. The model was simulated sequentially, considering pillar-by-pillar extraction, to estimate the vertical stress and factor of safety (FOS) on the working pillars. During depillaring on the dip side, the FOS of the working pillars was estimated to be more than 1.7. However, on the rise side, some of the goaf edge pillars, including barrier pillars, had a FOS in the range of 1.3 to 2.5, leading to excessive side spalling of pillars. Based on this analysis, it was suggested that the minimum FOS of the working pillars should be more than 1.5, preferably 2, as a design criterion for the panel. Using this criterion, the next panel layout was proposed and numerically simulated to ensure it met the design requirements. The proposed panel was then investigated during the depillaring operations, where no major strata-related issues were observed. The field observations, including the area of the first major fall and the subsidence profile, were largely in agreement with the numerical simulation results. © Society for Mining, Metallurgy & Exploration Inc. 2025.